The Effect of Micro-Enterprises on Poverty and Unemployment in the Philippines - Sarmiento, Allen Grace M. (Future Science / FSH-PH Publications, 2025)
The importance of micro-enterprises in economic growth cannot be overstated. Often, micro-enterprises are seen as a vital source of employment. However, the existence of poor people, as well as low educational attainment, poor health, low-level income, and an increase in the unemployment rate, remains obvious. The study investigates the effect of registered micro-enterprises on the numbers of unemployed and poor households in the Philippines. The study used panel regression as the primary statistical treatment to examine micro-enterprises effect on the number of poor households and unemployment in the 17 regions of the Philippines. The findings revealed that the number of poor households is significantly affected by the number of registered micro-enterprises under the random effect model. As for micro-enterprises effect on unemployment, the results demonstrate that the number of unemployed is considerably affected by the number of registered micro-enterprises under the fixed effect model. The study recommends promoting micro-enterprises laws, increasing financial support, and improving training programs for micro-enterprises.